2012
DOI: 10.1136/annrheumdis-2012-201295
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome and global expression profiling of Dupuytren's disease: systematic review of current findings and future perspectives

Abstract: Dupuytren's disease (DD) is a common fibroproliferative disorder affecting the palmar fascia, which may lead to permanent contracture of the affected digit. Profiling studies investigating DD at whole-genomic, transcriptomic and proteomic levels have been carried out, from which large numbers of candidate genes potentially involved in DD have been reported. This review focuses on identifying genes reported by multiple studies or validated by multiple experimental techniques, as well as signalling pathways sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 93 publications
(162 reference statements)
2
15
1
Order By: Relevance
“…Fibrogenic cytokines that cause growth and differentiation of fibroblasts and production of ECM, such as epidermal growth factor (EGF), transforming growth factor-alpha and –beta (TGF-α, TGF-β) and platelet-derived growth factor (PDGF), have been implicated in DD [26], [27]. Gene expression has also been investigated in various tissues or primary cells from DD patients using various experimental approaches and designs, and different gene expression platforms and methods of analysis [28]. Most have identified candidate genes, but many of the older gene expression studies did not have the sensitivity or depth of coverage [29].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fibrogenic cytokines that cause growth and differentiation of fibroblasts and production of ECM, such as epidermal growth factor (EGF), transforming growth factor-alpha and –beta (TGF-α, TGF-β) and platelet-derived growth factor (PDGF), have been implicated in DD [26], [27]. Gene expression has also been investigated in various tissues or primary cells from DD patients using various experimental approaches and designs, and different gene expression platforms and methods of analysis [28]. Most have identified candidate genes, but many of the older gene expression studies did not have the sensitivity or depth of coverage [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most have identified candidate genes, but many of the older gene expression studies did not have the sensitivity or depth of coverage [29]. Recent use of higher density arrays has confirmed and extended some gene expression profiles in DD patient tissues and identified additional candidate genes [28], [30], [31], [32]. These include genes associated with tissue remodelling such as matrix metalloproteinases [28], [29], [31], [33], [34], those which have roles in the ECM, including fibronectin ( FB1 ) laminins ( LAMB1 ), integrins and thrombospondin ( THDS2 ) [32] and others in which the link between the altered expression at both the transcriptional and translational levels like myoglobin and the tyrosine kinase orphan receptor 2 ( ROR2 ) is less clear in terms of pathogenesis [30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Other studies identified the candidate genes MafB, MMPs, TGF-β, ADAM 12, POSTN, TNC, ADAMTS3, BMP5, collagenases, α-smooth muscle actin, fibronectin, β1 integrin, laminin, tenascin C, Hsp47, collagen 1, ALDH1A1, IRX6, PRG4, ZF9, PDGF-β, and c-myc. [15][16][17][18][19][20][21] Most recently, a whole genome-wide association study performed in Europe, identified eleven single nucleotide polymorphisms (SNPs) from nine different loci, with six of the loci known to be involved in the Wnt signaling pathway. 22 Because many genetic studies fail replication, and the findings may differ among populations of people, we set out to confirm these findings in a North American population.…”
mentioning
confidence: 99%
“…Expression analyses in DD (by e.g. microarray or q-RT-PCR) [1827] have shown that these key pathways are indeed modulated, but do not always yield the same results: either different set of hits or different mode of expression (downregulation versus upregulation). Considering the heterogeneity among individuals and additional factors including biopsy material or comparison with carpal tunnel-derived fascia palmaris or “normal” adjacent tissue from DD patients, as well as the derivation of tissue fibroblasts, there is high variability in the outcomes.…”
Section: Molecular and Cellular Alterations In Dd Degenerationmentioning
confidence: 99%